Photos of threespine stickleback Gasterosteus aculeatus from the subarctic White Sea and table datasets in CIELAB values used for studying coloration - Nadtochii, Ekaterina (PANGAEA, 2025)
This dataset includes photographs of threespine stickleback (Gasterosteus aculeatus L.) collected in 2021 and 2023, along with raw data tables containing CIELAB color space (L*, a*, b*) values, to study pre-spawning coloration. In 2021, we made photos of sticklebacks from an experimental pool. Initially, approximately 1,100 threespine stickleback were collected from the Seldianaia Inlet on June 5, 2021, using a 7 m x 1.5 m beach seine. Spawning coloration was not observed at the time of capture. Then, fish were held in an experimental pool at the Educational and Research Station Belomorskaya of St. Petersburg State University, in Kandalaksha Bay, White Sea. The pool lacked substrate, and the water temperature was maintained at approximately 12°C under natural photoperiod conditions. Fish were held for several days to minimize stress. No breeding behavior was recorded during this experiment. Eleven days after capture, 34 females and 17 males were randomly selected for analysis. Sex was determined by observing inner mouth color (males: bright orange lips; females: pale lips) and confirmed by dissection. These fish were photographed. Individuals were photographed alive in a custom-designed wooden photo box. The camera (Canon EOS 650D) was positioned perpendicular to the shooting plane, with the lens 17 cm from the surface. Five fish were photographed at a time. Images were captured in .RAW format (3456 x 5184 pixels). In 2023 we photograhed wild fish from the Seldianaia Inlet. Thirty males and thirty females were collected from the Seldianaia Inlet on June 4, 2023, four days after their presence was noted near the university's educational and research station. Fish were collected by the same beach seine before active spawning and did not show clear signs of spawning coloration. Individuals were photographed alive in the same custom-designed wooden photo box as in 2021. The camera (RICOH WG-6) was positioned perpendicular to the shooting plane, with the lens 17 cm from the surface. Ten fish were photographed at a time. Images were captured in .JPEG format (5184 x 3888 pixels). Color correction was performed using a Datacolor SpyderCheckr24 color card, followed by processing in Adobe Lightroom and SpyderCheckr 1.3 software. All corrected images were saved in .JPEG format.ImageJ software was used to analyze the corrected images and extract the L*, a*, and b* values. Color was measured at eight standard sites (regions of interest) on each fish, covering different body parts. L*, a*, and b* values were recorded for each location. Thus, we have the raw data for 51 fish caught in 2021 from the experimental pool and for 60 fish caught in the field conditions in 2023 with the associated metadata for each subset.
Keywords: COLOR; fish; marine fish; stickleback; subarctic; White Sea